The incentives to North-South transfer of climate-mitigation technologies with trade in polluting goods - Matthieu Glachant; Julie Ing; Jean Philippe Nicolaï (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
The need to transfer climate mitigation technologies towards the developing world has been acknowledged since the beginning of climate negotiations. Little progress has however been made as shown by Article 10 of the Paris Agreement. One reason is that these technologies could become vital assets to compete on global markets. This paper presents a partial equilibrium model with two regions, the North and the South, and imperfect competition in the international polluting goods market to analyze the North's incentives to accept technology transfer. Results crucially depend on the existence of environmental cooperation. When both northern and southern governments set emission quotas non-cooperatively, inducing fewer global emissions is a necessary, but not sufficient condition for the North to accept the transfer. In contrast, when governments set quotas cooperatively, the North never accepts the transfer because it only leads to a partial relocation of pollutant goods production to the South. We derive the implications for the global regulation of climate change.
Keywords: D43; F18; Q5; 330; Technology transfer; Imperfect competition; Climate policy; Environmental cooperation; Cap and trade; Technologietransfer; Umwelttechnik; Internationale Klimapolitik; Internationale Zusammenarbeit; Unvollkommener Wettbewerb; Partielles Gleichgewicht